دراسة تجريبية على خلطة البيتون ذاتي الارتصاص المصنَّع من مواد محلية المنشأ - حويجة بسام; تريكية علي; خيربك زيد (Latakia University Journal -Engineering Sciences Series, 2016)
يتميز البيتون ذاتي الارتصاص SCC (self-compacting concrete) بالقدرة العالية على ملء القالب وقابلية المرور عبر الحواجز تحت تأثير وزنه الذاتي دون الحاجة إلى الرج مما يخفض عدد العمالة المطلوب ويقلل من الضجيج المترافق مع عملية الرج، وتركز التطبيقات الحديثة على تحسين مواصفة الأداء العالي والمقاومة وسرعة الإنشاء. يقدم هذا البحث دراسة تجريبية للحصول على خلطة البيتون ذاتي الارتصاص (SCC) المصنعة من مواد محلية المنشأ، تتضمن إجراء التجارب اللازمة على خلطة البيتون المقترحة والمعتمدة في الكودات العالمية، وتحدد هذه التجارب الخصائص الأساسية لـ (SCC) في الحالة الطرية، كما تم تحديد مقاومة (SCC) على الضغط وتحديد قيمة معامل المرونة (E) ورسم منحنيات السلوك. تم الوصول إلى خلطات حققت المعايير والشروط العالمية وأجريت جميع التجارب في مخبر كلية الهندسة المدنية في جامعة تشرين. Featuring a self-compacting concrete (SCC) high capacity to fill the mold and passing ability through barriers under the influence of self-weight without vibration, thereby reducing the required labour and reduces the noise associated with vibration. Modern applications focused on improving the specifications of high performance, resistance and speed of construction. The research presents an experimental study for an (SCC) mix produced from local materials, including the necessary tests on the proposed concrete mix, which approved in the global codes. These experiments determine the basic characteristics of (SCC) in fresh case were also identified pressure resistance of (SCC) and determine the value of the modulus of elasticity (E) and the behavior curvatures. All mixes have been achieved global standards and conditions, and the required experiments were done in the laboratory of civil engineering faculty at Tishreen University.